2017
DOI: 10.1186/s12885-017-3682-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cervical human papillomavirus (HPV) infection and squamous intraepithelial lesions (SIL) among a cohort of HIV-infected and uninfected Ghanaian women

Abstract: BackgroundThere is limited data in Ghana on the epidemiology of HPV and cervical neoplasia and their associations with HIV. This study aimed to compare among HIV-1 seropositive and HIV-seronegative Ghanaian women: (1) the prevalence, genotype distribution and risk factors associated with cervical HPV infection; and (2) the prevalence and risk factors associated with abnormal cervical cytology.MethodsA comparative frequency-matched study was conducted in a systematic sample of women aged ≥18 years attending HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
40
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 54 publications
10
40
2
1
Order By: Relevance
“…Indeed, the overall prevalence of 34.4% carriage of HR-HPV in these women was close to that of 38.3% in Burkina Faso [5] , 35.0% in England [9] , 33.8% in Costa Rica [10] and 33.2% in Benin [11] . On the other hand, it was lower than those of 75.0% in Ghana [12] , 74.0% in Tanzania [13] and 54.0% in South Africa [14] , 41.5% in Burkina Faso [7] obtained from studies of younger populations with a mean age of less than 30 years while that of our study was 35.5 ± 9.5 years.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Indeed, the overall prevalence of 34.4% carriage of HR-HPV in these women was close to that of 38.3% in Burkina Faso [5] , 35.0% in England [9] , 33.8% in Costa Rica [10] and 33.2% in Benin [11] . On the other hand, it was lower than those of 75.0% in Ghana [12] , 74.0% in Tanzania [13] and 54.0% in South Africa [14] , 41.5% in Burkina Faso [7] obtained from studies of younger populations with a mean age of less than 30 years while that of our study was 35.5 ± 9.5 years.…”
Section: Discussioncontrasting
confidence: 81%
“…Among women recruited in Tenkodogo, HPV genotypes 16 and 18 covered by currently vaccines available in Burkina Faso, accounted for 4.1% and 1.4% respectively. The prevalence of HPV18 obtained is lower than that of 5.5% in Great Britain [2] , 10,6% in Ghana [12] , 14.8% in Bobo-Dioulasso [6] , 14.3% [8] and 5.1% [7] in Ouagadougou. The results of these studies thus show a regional difference in the distribution of HPV 18.…”
Section: Discussionmentioning
confidence: 97%
“…When cancer symptoms are noticed, knowledge of the importance of early detection can be lacking [9][10][11]. Cancer awareness is important overall, and especially in high-risk individuals such as people living with HIV/AIDS (PLHIV), a prevalent group in many SSA settings with raised risks of several cancers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas several studies [25][26][27] reported that women's number of partners and history of STIs were associated with cervical cancer among the women in South Africa. However, the study of Obiri-Yeboah 28 reported that age of women and circumcision status of main sexual partner were associated with cervical cancer, but no association was found with number of partners.…”
Section: Discussionmentioning
confidence: 93%